Peninjauan Kembali Demi Keadilan - Alfret, Alfret (UI Scholars Hub, 2023)
Abstract As the world of law develops, there are more and more new provisions related to the implementation of Judicial Review (PK). Some concrete examples related to the development of PK provisions themselves are that a PK can only be carried out once. Apart from that, there is also a provision that the public prosecutor cannot carry out request for reconsideration. This raises the question of whether these restrictions do not conflict with the principles of justice. This research was studied using normative juridical methods based on existing legal provisions and decisions. So the results of this research show that PK restrictions can be distorted for the sake of justice so that legal provisions related to judicial review should not contain restrictions that make it difficult for justice seekers. Keywords: Judicial Review; Justice; Court ruling